Implementation Of Ischemic Compression Technique And Myofascial Release Technique In Reducing Disability In Myofascial Pain Syndrome Upper Trapezius Muscle - Prayogo, Dadan; Sadu, Bernadus; Wicaksono, Utomo; Anggelina, Denastasia Deswita; Prasana, I Gede Eka Juli (Sean Institute, 2024)
Patients with myofascial pain syndrome of the upper trapezius muscle are a population that is widely found by various groups, one of which is in stone crusher workers. Myofascial pain syndrome of the upper trapezius muscle is an implication of the presence of trigger points in the taut band caused by adhesion to the myofascial structure. This study is an experimental study using pre and post test control group design which aims to compare the better intervention between the provision of myofascial release technique and ischemic compression technique on improving functional ability in cases of myofascial pain syndrome of the upper trapezius muscle. The sample in this study amounted to 22 people and was divided into two application groups with each group totaling 11 people. The results of the related t-test showed that both applications could reduce significant disability (p < 0.05), and the results of the independent t-test showed that each group could reduce disability in cases of myofascial pain syndrome of the upper trapezius muscle but did not show a significant difference, p value = 0.41 (p> 0.05). Conclusion: the application of myofascial release technique is as good as ischemic compression technique and can be used as a physiotherapy technique in reducing disability in myofascial pain syndrome of the upper trapezius muscle.